INTERACTIVE VIRTUAL PLATFORM FOR ROBOTICS EDUCATION: SOFTWARE ARCHITECTURE AND FUNCTIONAL MODELS - Buranova Gulnora Yodgorovna; Barnoyeva Zubayda Erkin qizi (Modern American Journals, 2025)
This article analyzes the software architecture and functional models of a virtual platform designed for modern, remote, and interactive teaching of robotics. The platform includes interactive lessons, a block-based coding environment, real-time 2D/3D simulators, an automated test evaluation system, and a personal project workspace for users. The software solutions are integrated using front-end technologies (HTML5, CSS, JavaScript), back-end frameworks (Python/Flask or Django), as well as WebGL, Blockly, and Arduino emulators. The article thoroughly explores the platform's technical requirements, inter-module integration, user experience (UX), and its advantages in developing students' independent engineering thinking. The research results contribute to accelerating digital transformation in education, enabling robotics instruction without hardware components, and offer new approaches to software development in educational technology.